2009
DOI: 10.1007/s11064-009-9992-x
|View full text |Cite
|
Sign up to set email alerts
|

Cografted Wharton’s Jelly Cells-derived Neurospheres and BDNF Promote Functional Recovery After Rat Spinal Cord Transection

Abstract: An animal model of transected spinal cord injury (SCI) was used to test the hypothesis that cografted human umbilical mesenchymal stem cells-derived neurospheres (HUMSC-NSs) and BDNF can promote morphologic and functional recoveries of injured spinal cord. In vitro, HUMSC-NSs terminally differentiated into higher percentages of cells expressing neuronal markers: beta-tubulin III and MAP2ab by the supplement with BDNF. Following grafted into injured spinal cord, very few grafted cells survived in the HUMSC-NSs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 20 publications
(25 reference statements)
0
27
0
1
Order By: Relevance
“…Some studies have shown the survival of numerous transplanted cells for periods as long as 4 mo, even though no immunosuppression was used (6,59,97). Contrarily, in similar animal models, few transplanted cells could be identified a few weeks after transplantation in immunosuppressed animals (98). Further studies are therefore required to clarify whether immunosuppression is a help or a hindrance in obtaining the most beneficial outcomes in xenotransplantation experiments.…”
Section: Potential Shortcomings Of the Use Of Huc-mscsmentioning
confidence: 99%
“…Some studies have shown the survival of numerous transplanted cells for periods as long as 4 mo, even though no immunosuppression was used (6,59,97). Contrarily, in similar animal models, few transplanted cells could be identified a few weeks after transplantation in immunosuppressed animals (98). Further studies are therefore required to clarify whether immunosuppression is a help or a hindrance in obtaining the most beneficial outcomes in xenotransplantation experiments.…”
Section: Potential Shortcomings Of the Use Of Huc-mscsmentioning
confidence: 99%
“…Zhang et al [83] , used an animal model of transected SCI to test the hypothesis that cografted human umbilical mesenchymal stem cells-derived neurospheres (HUMSC-NSs) and BDNF can promote morphologic and functional recoveries of the injured spinal cord. Recovery of hindlimb locomotor function in SCI rats was significantly enhanced in human umbilical cord mesenchymal stem cells-grafted animals at five weeks as compared to control sham-grafted animals [84] .…”
Section: Downregulation Of Neuronal Apoptosismentioning
confidence: 99%
“…In this respect, it is worth mentioning that MSCs can self-renew and differentiate into tissues of mesodermal origin. 37,38 However, some data also suggest their ability to turn into other cell types, such as glial and neural cells, [46][47][48][49] or pancreatic [50][51][52] and hepatocyte-like cells. 53,54 Despite considerable debate regarding the ability of MSCderived cells to express markers' characteristic for fully differentiated ecto-and endodermal lineages, there is growing evidence supporting MSCs potential for generating cell types of multiple lineages suitable for cell therapy in various degenerative and metabolic conditions, including diabetes (reviewed in literatures 32,55,56 ).…”
Section: Mesenchymal Stem Cells and Their Role In Diabetesmentioning
confidence: 99%